Advancing Oceanic Studies with HyperOCR Sensors and Non-Negative Matrix Factorization: A Cost-Effective, Data-Driven Approach for Analyzing Light in Marine Water Column (Global Journal of Science Frontier Research, 2024)
Understanding the intricate dynamics of ocean biogeochemistry is crucial for deciphering its role in climate change Our study addresses this challenge by integrating advanced computational techniques and innovative sensor technology to enhance remote sensing capabilities Drawing on recent insights into the vast carbon reservoirs within the ocean particularly within the dissolved organic matter DOM pool we highlight the pressing need for comprehensive spatial and temporal understanding facilitated by a combination of satellite and in situ data However existing remote sensing methods face limitations in capturing subsurface processes hindering our ability to grasp carbon fluxes within the oceanic water column fully Recent advancements in remote sensing offer promising avenues for addressing these challenges